Studi kekuatan kekerasan dan kekuatan impact pada komposit diperkuat serat sansevieria dengan variasi penambahan amilum 6%-10% - Edi Widodo; wistyo nugroho, wistyo nugroho (Jurnal Teknik Mesin Indonesia, 2025)
Natural fiber reinforced polymer composites have become one of the areas of research that attract attention because of their superior and environmentally friendly mechanical properties. This study aims to determine the effect of adding starch 6%, 7%, 8%, 9%, 10% on the characteristics of the mechanical properties of composites reinforced with sansevieria fibers. The manufacture of this composite uses the hand lay up method with a fiber weight fraction volume of 30% and alkali treatment of sansevieria fibers with a concentration of 5% NaOH for two hours. This alkali treatment aims to reduce the content of lignin, hemicellulose, and dirt layers on the fiber surface. Testing the characteristics of mechanical properties in this study is the impact test and Shore D hardness test. In the good impact test results without the addition of starch, because the increasing concentration of starch can reduce the density of molecular bonds in the polymer matrix, so that the bond strength between molecules decreases. While the results of the Shore D hardness test are better adding starch, because starch acts as a filler that reduces local deformation on the composite surface when tested with an indenter on the Shore D hardness tester.